Reducing poverty in the Caribbean : implications for health and education - Greene, Edward (PAHO WashingtonUS, 1996)
Focuses on issues in health and education and their possible role in strategies for poverty reducation in the Caribbean. Examines the major methods of investigating poverty. Accepts the measure of absolute poverty as the most expedient for comparative analysis.